MOTIVATION OF NURSES IN PROVIDING FIRST AID TO PATIENTS EXPERIENCING CARDIAC ARREST - Putri, Ivananda Siera Lisna; Okviasanti, Fanni; Ilkafah, Ilkafah; Harianto, Susilo; Purwanto, Cucuk Rahmadi; Muhalla, Hafna Ilmy; Nasir, Abd; Iswatun, Iswatun (Journal of Vocational Nursing, 2024)
Introduction: Cardiac arrest is often found in patients in the inpatient room of Ibnu Sina Hospital, Gresik. Nurses as the first responders who find cardiac arrest in the treatment room must have high work motivation to provide first aid to patients before the code blue team arrives. The purpose of this study was to obtain a description of the work motivation of nurses in providing first aid to patients experiencing cardiac arrest in the inpatient room of Ibnu Sina Hospital, Gresik. Methods: This study used quantitative research with a descriptive approach. The sample of this study was some of the nurses in the inpatient room of Ibnu Sina Hospital, Gresik, which was taken using a purposive sampling technique of 55 respondents who had met the inclusion and exclusion criteria. The data collection instrument used a questionnaire. The data was processed using SPSS v.25 for frequency and percentage. Results: The results showed that most respondents had good work motivation, with 53 respondents (96.4%) providing first aid to patients experiencing cardiac arrest. Conclusions: Nurses are expected to maintain work motivation in providing first aid to patients experiencing cardiac arrest, especially in inpatient rooms, through good collaboration between teams, always receiving positive support in the form of recognition of achievements from colleagues, and increasing periodic certification training related to handling cardiac arrest patients because patient safety is the main priority.